Larangan Bid’ah dalam Kitab Arbain Nawawi:: Analisis Hadis Nabi Tentang Larangan Melakukan Perbuatan Bid’ah dan Implementasinya Pada Kaidah Uluhiyyah - Irodat, Ahsan (Al Ashriyyah, 2023)
The Book of Hadith Arba'in is a work written by a great scholar, who has a high reputation among Muslims, namely Imam Nawawi. In the book of Arba'in there are also several other priests such as Al-Ajurri, Al-Baihaqi, Ash-Shabuni, Al-Hakim, Ad-Daruquthni, Ath-Tabari, As-Suyuthi, Ibn Hajar Al-Asqalani and in addition to those who number up to dozens of books of Arbain. And the book of arba'in is already very widely known and fragrant until now. The basis of this book is "Al-Ahadith Al-Kulliyah" dictated by Imam Al-Hafizh Abu Amr bin Ash-Shalah, which is a collection of 26 hadiths that are dense and concise. Then Imam Nawawi fulfilled it into 42 hadiths and named it Al-Arba'in. This simple paper uses the library search method, and this type of research is a qualitative method. The discussion of this paper is divided into several sub-discussions: introduction, brief biography of Imam Nawawi, understanding of monotheism uluhiyyah, prohibiting bid'ah in religion. In this conclusion, Imam Nawawi chose the hadith that became the foundation of Islam in compiling his Arba'in book, Imam Nawawi's foresight in conceptualizing the chapters of the book.